2017
DOI: 10.21894/jopr.2017.2903.11
|View full text |Cite
|
Sign up to set email alerts
|

Emissions Analysis on Diesel Engine Fueled With Palm Oil Biodiesel and Pentanol Blends

Abstract: EMISSIONS ANALYSIS ON DIESEL ENGINE FUELED WITH PALM OIL BIODIESEL AND PENTANOL BLENDS ITRODUCTIONEscalating environmental issues coupled with depletion in petroleum resources have paved the way for global efforts to search for eco-friendly fuels (Amirnordin et al., 2013). Automobiles are widely acknowledged as the major source of greenhouse gas emissions. Diesel engines play a significant role in the power and automobile sectors of industry largely because of its durability and economy. However, diesel engine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(23 citation statements)
references
References 12 publications
1
22
0
Order By: Relevance
“…But very few works have been carried out on neat alcohol-biodiesel (Venkata Ramanan and Yuvarajan, 2015a, b;Devarajan et al, 2017;. Dual-fuel blending is an effective technique for reducing the emissions from diesel engines (Radhakrishnan et al, 2017;Santhosham and Aghalayam., 2016;Devarajan et al, 2017a, b). Hence in this work, the author makes the effort to reduce the emissions of neat biodiesel fueled engine by adding acetone to biodiesel as an emulsion.…”
Section: Introductionmentioning
confidence: 99%
“…But very few works have been carried out on neat alcohol-biodiesel (Venkata Ramanan and Yuvarajan, 2015a, b;Devarajan et al, 2017;. Dual-fuel blending is an effective technique for reducing the emissions from diesel engines (Radhakrishnan et al, 2017;Santhosham and Aghalayam., 2016;Devarajan et al, 2017a, b). Hence in this work, the author makes the effort to reduce the emissions of neat biodiesel fueled engine by adding acetone to biodiesel as an emulsion.…”
Section: Introductionmentioning
confidence: 99%
“…However, Sridhar et al (2018) reported that 1-pentanol/WCO biodiesel blends decreased the emissions of NOx, HC, and CO simultaneously compared to neat biodiesel, with a slight penalty of BTE. It was also observed by Radhakrishnan et al (2017) that for palm oil biodiesel/pentanol blends (B90P10 and B80P20), CO, HC, NOx, and smoke emissions were reduced compared to neat palm oil biodiesel.…”
Section: Combustion and Emission Characteristicsmentioning
confidence: 89%
“…Biodiesel, which is composed of longer fatty acids or more saturated fatty acids, appears to have greater kinematic viscosity [30]. Hence, biodiesel made from palm oil has greater kinematic viscosity than those biodiesels made from corn oil, canola oil, rapeseed oil, and soybean oil [26,31], primarily due to the higher content of saturated fatty acids of the PME in those biodiesels. Biodiesel consisting of less unsaturated fatty acids content was produced from palm oil with water content either relatively higher or lower than 0.05 wt.…”
Section: Kinematic Viscosity Of the Biodieselmentioning
confidence: 99%
“…from corn oil, canola oil, rapeseed oil, and soybean oil [26,31], primarily due to the higher content of saturated fatty acids of the PME in those biodiesels. Biodiesel consisting of less unsaturated fatty acids content was produced from palm oil with water content either relatively higher or lower than 0.05 wt.…”
Section: Kinematic Viscosity Of the Biodieselmentioning
confidence: 99%